APAKAH KEPUASAN KERJA DAPAT MEMEDIASI EFEK MUTASI TERHADAP KINERJA KARYAWAN? - Arwinni Ratu Masturahman H; Yana Fajriah; Muhammad Tafsir (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research is to test the capability of job satisfaction as a mediator in analysing the relationship between job transfer and employee performance. This research is quantitative based and uses primary data. The population of this study were 140 employees of PT Paragon Technology and Innovation Makassar Branch, the sample withdrawal used total sampling with a total sample size of 140 employees. Structural equation model analysis is used with the assistance of structural Partial Least Square (PLS). The results of this study indicate that job mutation has a positive and significant effect on job satisfaction and employee performance. On the other hand, the results obtained if the job satisfaction felt by employees is at a high level so that it is proven to improve employee performance. The role of satisfaction in this study is evidenced as a mediator. Keywords : Employee performance, job mutation, job satisfaction